From collectivism towards segmentalism: Institutional change in German vocational training - Kathleen Ann Thelen; Marius R. Busemeyer (Max Planck Institute for the Study of Societies, 2008)
This paper argues that the German system of vocational training is undergoing subtle but significant changes from a mainly collectivist system to a more segmentalist one. To make the argument, the paper first discusses the two logics of collectivism and segmentalism, and how the German system is characterized by longstanding tensions between competing collectivist and segmentalist interests. In the empirical section, recent trends in the German system are portrayed to show that the system's segmentalist dimension has been strengthened at the expense of its collectivist dimension. These trends can be seen from developments in the participation of firms in training and from the changing politics of vocational training reform. To buttress our argument, we present three case studies on the debate over the modularization and Europeanization of vocational training, on the (re)introduction of two-year apprenticeships and on the unfolding conflict on vocational exams respectively. Before we conclude, we highlight parallels in contemporary trends in vocational training and changes in other realms of the German political economy. – – Dieses Papier dokumentiert den graduellen, aber transformativen Wandel des deutschen Berufsbildungssystems von einem kollektivistischen zu einem stärker segmentalistischen Modell. Zunächst wird gezeigt, dass die beiden Logiken des Kollektivismus und des Segmentalismus in der Geschichte der beruflichen Bildung schon immer in einem Spannungsverhältnis standen. Im empirischen Teil wird gezeigt, dass die segmentalistische Dimension während der letzen drei Jahrzehnte gegenüber der kollektivistischen an Bedeutung gewonnen hat. Dies wird anhand der Entwicklung der Ausbildungsbeteiligung von Unternehmen sowie der Politik der beruflichen Bildung dokumentiert. Insbesondere werden drei Fallstudien zur Debatte über Modularisierung und Europäisierung der beruflichen Bildung, zur (Wieder-)Einführung zweijähriger Ausbildungsberufe und zum sich anbahnenden Konflikt über die Organisation von Prüfungen präsentiert. Abschließend werden Parallelen zwischen dem Wandel der beruflichen Bildung und den Arbeitsbeziehungen im Allgemeinen herausgearbeitet.
Keywords: 370